MENSTIMULASI PERKEMBANGAN MOTORIK HALUS MELALUI MEDIA LOOSE PARTS DI PAUD KELOMPOK BERMAIN PAMMASE DESA MAMMI - Hasbi, Nurul Amaliah; M, Munawarah; M, Murniati; R, Rusniati (EDUCHILD (Journal of Early Childhood Education), 2024)
Physical-motor development is a process in which a person develops through a response that results in a coordinated, organized and integrated movement, then skills can be seen as the basis for a person's success in performing motor skills, natural and synthetic materials around the PAUD school environment. The purpose of this research is to stimulate children's fine motor development through loose parts media and to what extent educators stimulate this development. The type of research used is qualitative research, which builds meaning based on data in the field. The research subjects were students in the Pammase Play Group Early Childhood Education. This qualitative research procedure produces descriptive data in the form of written or spoken words of observable people and behavior. Techniques used in data collection in the form of observation, and interviews and documentation. Data analysis was carried out by giving meaning to the data that was successfully collected. And from these data can be drawn conclusions. Indicators of success in this study are: (1). Achieving a stimulus for the physical development of fine motor skills in children through loose parts mesia in Pammase Play Group Early Childhood Education, Mammi Village, Binuang District, Polewali Mandar Regency, (2) The role of educators and students in stimulating the physical development of children's fine motor skills through loose parts media in KB Pammase Mammi Village, Binuang District, Polewali Mandar Regency.